Inter-observer variability of the histological classification of lupus glomerulonephritis in children. (October 2017) - Oni, L; Beresford, M W; Witte, D; Chatzitolios, A; Sebire, N; Abulaban, K; Shukla, R; Ying, J; Brunner, H I
The gold standard for the classification of lupus nephritis is renal histology but reporting variation exists. The aim of this study was to assess the inter-observer variability of the 2003 International Society of Nephrology/Royal Pathology Society (ISN/RPS) lupus nephritis histological classification criteria in children. Histopathologists from a reference centre and three tertiary paediatric centres independently reviewed digitalized renal histology slides from 55 children with lupus nephritis. Histological ISN/RPS Class was assigned and features scored; lupus nephritis-activity [scored 0–24], lupus nephritis-chronicity [0–12] and tubulointerstitial activity [0–21]. In the cohort (73% females), the age at the time of biopsy was 15.5 ± 0.39 (mean ± standard error) years. Based on the reference centre, 42% (23/55) had ISN/RPS Class IV with lupus nephritis-activity score 4.23 ± 0.50, lupus nephritis-chronicity 1.81 ± 0.18 and tubulointerstitial activity 4.45 ± 0.35. There were 4–54 (mean 16.7) glomeruli per biopsy. Pathologists had fair agreement for ISN/RPS assignment (kappa; 0.26 ± 0.12), lupus nephritis-chronicity (intra-class correlation 0.36 ± 0.09) and tubulointerstitial activity (0.22 ± 0.09) scores. There was good agreement for lupus nephritis-activity scores (intra-class correlation 0.69 ± 0.06). When categorized into proliferative and non-proliferative disease, poor agreement among sites remained (kappa 0.24 ± 0.11). Despite unified criteria for the interpretation of histological features of lupus nephritis, marked reporting variation remains in clinical practice. As proliferative lupus nephritis is managed more intensively, this may influence renal outcomes.